Investigation of the Motivational Persistence Levels of the Students Studying at the Faculty of Sport Sciences According to Some Demographic Characteristics - Onturk, Yavuz; Yildiz, Yasin (Asian Journal of Education and Training, 2020)
This study was carried out to investigate the motivational persistence levels of students who received sports education and examine in terms of some demographic variables. In the study, the “Motivational Persistence Scale” consisting of long-term purposes pursuing, current purposes pursuing, recurrence of unattained purposes sub-dimensions was used to measure motivational permanence of the students. The research group consisted of 347 students who voluntarily participated from Faculty of Sport Sciences of Mugla Sitki Kocman University. The data were analyzed through the statistical package program SPSS 22.0. The demographic information of the students was determined with descriptive statistics. Independent T-test was used to compare the subscale scores by gender, and One Way ANOVA analysis was used to compare the age groups and overall academic grade averages. The results of the analyzes showed that the motivational persistence levels of the students of the faculty of sport sciences are medium and close to high. In addition, there was no significant difference in terms of the age variable, but it was found that students aged 25 and over were more motivated. Further, it has been observed that the students whose academic grade average was 1.00 to 1.99 were higher than the students whose grade average was between 3.00–4.00.